2008
DOI: 10.1021/om701236k
|View full text |Cite
|
Sign up to set email alerts
|

Different Modes of Reactivity of Cp*W(NO)(alkyl)(η3-allyl) Complexes with Cyclic Amines: The Influence of the Allyl Ligands

Abstract: Metathesis reactions between Cp*W(NO)(CH 2 EMe 3 )Cl (E ) C or Si) and a variety of bis(allyl)magnesium reagents lead to the formation of 18e Cp*W(NO)(alkyl)(η 3 -allyl) complexes. The compounds 5), and Cp*W(NO)(CH 2 CMe 3 )(η 3 -CH 2 CHCH 2 ) (6) have thus been synthesized in moderate yields. The solid-state molecular structures of 3, 4, 5, and 6 feature σ-π distorted allyl ligands in the endo conformation. Complex 1 effects the concurrent N-H and R-C-H activations of pyrrolidine and piperidine under ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…the formation of an N-C bond between the nitrogen atom of the piperidine ligand and the carbon atom of the allyl ligand. This reaction may occur at the molybdenum atom in a similar way as the formation of a C-C bond recently observed by Legzdins et al during the reaction of an allyl complex of tungsten with cyclic amines [20].…”
Section: Introductionsupporting
confidence: 63%
“…the formation of an N-C bond between the nitrogen atom of the piperidine ligand and the carbon atom of the allyl ligand. This reaction may occur at the molybdenum atom in a similar way as the formation of a C-C bond recently observed by Legzdins et al during the reaction of an allyl complex of tungsten with cyclic amines [20].…”
Section: Introductionsupporting
confidence: 63%
“…The thermodynamically controlled protonation of 1 results in the regioselective addition of a proton to form primarily the η 2 -benzenium complex 2A. Previously, we, as well as the Legzdins group, 29,30 reported that allyl complexes of W(NO) systems were hyperdistorted, with one terminus showing a W− C bond length considerably longer than the other. Extensive solid-state molecular structure determinations show that where the W−C bond lengths of the two carbons coordinated to the tungsten are typically ∼2.3 Å, the third allyl carbon (localized carbocation) is ∼2.6−2.8 Å from the tungsten center.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The solvent was removed from the eluate in vacuo to give Cp*W­(NO)­(CH 2 CMe 3 )­(η 3 -CH 2 CHCHPh) ( 1 ) as an orange solid (1.975 g, 31% yield). Characterization data for 1 have been previously reported …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Characterization data for 1 have been previously reported. 15 Preparation of Cp*W(NO)(CH 3 )(η 3 -CH 2 CHCHPh) (2). In a glovebox, a Parr 5500 pressure reactor was charged with a sample of 1 (0.600 g, 1.17 mmol) and cyclohexane (ca.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation